Hubungan Kepatuhan Diet Dan Asupan Kalium Dengan Kadar Kalium Pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa Rawat Jalan Di RSUD Kabupaten Sukoharjo - Annisa, Hilma, Endang Nur W, SST, M.si Med, dr. Listiana Dharmawati,. M.Si (2016)
Background : Chronic renal failure (CRF) is a clinical syndrome caused by deterioration in kidney function. Hemodialysis therapy should be run regularly in order to maintain a stable renal function. Giving diet in renal failure, including potassium restriction is indispensable to control potassium due to disturbances in kidney function that can lead to hyperkalemia. Objective : To determine the relationship of dietary compliance and potassium intake to potassium level in outpatient with CRF on hemodialysis therapy at Sukoharjo general hospital. Research methods : Analytical observation study with cross-sectional design was performed. 31 subjects were selected using consecutive sampling technique. Dietary compliance and potassium intake data were obtained from interviews using dietary compliance questionnaire and semiquantitative food frequency questionnaire, respectively. The potassium level was obtained from hospital medical records. All data was analyzed using rank spearman test since they were not normally distributed. Result : Most of the subjects were in noncomplience level (48.4%). Subjects with less potassium intake were 48.4 %. However, all subjects have normal circulating potassium level (100%). There is a relationship between potassium intake and potassium level (p=0.000). There is no relationship between dietary compliance and potassium level (p= 0.163). Conclution : There is a relationship between potassium intake and potassium level. However no relationship between dietary compilance and potassium level was observed in outpatient with CFR on hemodialysis therapy at Sukoharjo general hospital.